2012
DOI: 10.3109/09638288.2012.687028
|View full text |Cite
|
Sign up to set email alerts
|

Foot placement patterns of female rollator users with multiple sclerosis in the community

Abstract: Foot placement variability appears to be influenced by the walking environment of MS patients. Therefore, an enhanced understanding of walker-user interactions in relation to the environment must be established in order to improve mobility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Therefore other mechanisms than hip muscle activity must have prevented increased pelvic movement and consequently trunk sway during rollator walking. Chee et al (2013) investigated rollator use in multiple sclerosis patients and concluded that the device would "compensate for hip abductor weakness by providing improved frontal plane stability through upper extremity control". Tung et al (2014a,b) investigating rollator use in balance impaired subjects and healthy subjects under challenging balance conditions also concluded that "the upper limbs play a greater roll in controlling frontal plane balance during rollator assisted walking when lower-limb balance capabilities are limited or impaired".…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore other mechanisms than hip muscle activity must have prevented increased pelvic movement and consequently trunk sway during rollator walking. Chee et al (2013) investigated rollator use in multiple sclerosis patients and concluded that the device would "compensate for hip abductor weakness by providing improved frontal plane stability through upper extremity control". Tung et al (2014a,b) investigating rollator use in balance impaired subjects and healthy subjects under challenging balance conditions also concluded that "the upper limbs play a greater roll in controlling frontal plane balance during rollator assisted walking when lower-limb balance capabilities are limited or impaired".…”
Section: Discussionmentioning
confidence: 99%
“…The specific aims of rollator use vary depending on the patient diagnosis. For example, in the elderly or patients with neurological disease such as multiple sclerosis, rollators are used to increase walking endurance and muscle strength or to improve balance (Chee et al, 2013;Vogt et al, 2010;Braun et al, 2014). Following surgery, reduced weight bearing or pain may be treatment goals (Smith et al, 2012), whereas in patients with chronic obstructive pulmonary disease improvement of functional exercise capacity and reduction of dyspnoea can be the objectives (Gupta et al, 2006).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…However, complex walking tasks such as opening a door were found to lead to the impossibility to open and pass through a door with a rollator, because of the rigid rear wheels. Chee et al [11] investigated the step width, the variability of step width and velocity of two community-dwelling rollator users with multiple sclerosis (MS) by comparing their performance in the laboratory and outdoor walking environment including an urban pavement, a ramp and pedestrian crossing, using an instrumented rollator. The results suggest that the outdoor walking environment may affect foot placement patterns, and hence potentially, trip risk.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the recent advances in low-cost computing and sensing, there is no data on the patterns of use of rollator devices outside of controlled environments, whereas in other areas of mobility aids research such as wheelchairs the usage and activity levels can be measured by accelerometers and inertial measurement units (IMUs) [13][14][15]. This is very surprising, particularly given the high prevalence of rollators amongst older people and recent studies that indicate the potential for increased trip or fall risk outside of the laboratory [11,12]. Indeed, even basic information on the extent to which prescription of such devices leads to increased mobility is absent.…”
Section: Introductionmentioning
confidence: 99%